THE INFLUENCE OF MANAGERIAL COMPETENCE AND PRINCIPAL MOTIVATION ON TEACHER PERFORMANCE AT SMA MUHAMMADIYAH 2 PALEMBANG - Hidayat, Taufik; Harto, Kasinyo; Hartatiana, Hartatiana (Jurnal Konseling Pendidikan Islam, 2025)
Teacher performance is a primary determinant of instructional quality, while principals shape school outcomes through managerial competence and motivational drive. This study examines the partial and joint effects of principal managerial competence and principal motivation on teacher performance and identifies the dominant predictor at SMA Muhammadiyah 2 Palembang. Using a quantitative correlational design with a census approach (N=30 teachers), data were collected via a closed-ended five-point Likert questionnaire. All items met validity criteria (item–total r > .444, α=.05, two-tailed) and showed acceptable reliability (α=.791–.887). Assumption checks indicated normal residuals (Kolmogorov–Smirnov p=.200), no multicollinearity (tolerance=.419; VIF=2.388), and homoskedasticity (random scatterplot). Multiple regression revealed significant positive effects of both predictors on teacher performance: managerial competence (β=.755; t=9.015; p<.001) and principal motivation (β=.250; t=2.982; p=.006). The model explained a large share of variance (R²=.921; Adj. R²=.915) and was jointly significant, F (2,27) =156.621; p<.001). Findings indicate managerial competence is the dominant predictor; therefore, strengthening data-driven planning, role clarity, decision protocols, and monitoring–evaluation cycles linked to academic supervision should be integrated with fair, inclusive motivational mechanisms. Limitations include the cross-sectional, single-site design, small sample, and self-report measures. Future research should adopt multi-site, longitudinal, and multi-source designs and test mediators (e.g., teacher motivation/school climate) and moderators (e.g., tenure/certification) to deepen and generalize these conclusions.